Panel prefabricado de madera, lámina de policarbonato alveolar y lámina contrachapada para muros no estructurales (2017)
This monograph explains the solution of a problem on site or during the life cycle of the building. As it affects each one of them, at run time and costs, are points that must be considered. It will include elaboration of prototype, the step by step with photographic record with its respective description, planimetry and constructive details, for the reader to understand easily. At the end of the analysis, tabulation and results